Analyzing the Impact of Tax Administration on Economic Performance: An Examination of the Cameroon Tax System on the Economy - William, Ndiapa Sigalla (Journal of Emerging Markets and Management, 2025)
Regional economic disparities globally stem from variations in sectoral development among countries, manifested through differences in economic growth, infrastructure, living standards, and national income. Taxation serves as a crucial mechanism for national regulation and economic development, involving revenue collection and reinvestment into infrastructure, public utilities, defense, and welfare services. The effectiveness of these initiatives depends significantly on tax administration efficiency. This study examines the impact of tax administration on economic performance in Cameroon, employing a mixed-methods approach that analyzes historical revenue allocation between 2014 and 2024, budget implementation, and economic outcomes. Findings reveal a disconnect between increasing tax revenues and economic development indicators, with significant challenges including a narrow tax base of 73% of non-oil tax revenue from just 0.5% of businesses, administrative inefficiencies, and misallocation of resources. Despite digital reforms reducing tax compliance time from 1300 to 624 hours between 2007 and 2020, infrastructure development remains below regional standards. The study proposes a comprehensive framework linking tax administration efficiency to economic indicators and recommends context-specific reforms including broadening the tax base through informal sector integration, enhancing transparency in revenue allocation, implementing targeted digital solutions for rural areas, and strengthening institutional capacity. These findings contribute to understanding how developing economies can transform tax administration into sustainable economic growth.